The impact of potentially traumatic events on the mental health of males who have served in the military: Findings from the Australian National Survey of Mental Health and Wellbeing. (July 2017) - Wade, Darryl; Mewton, Louise; Varker, Tracey; Phelps, Andrea; Forbes, David
Objective: The study investigated the impact of potentially traumatic events on mental health outcomes among males who had ever served in the Australian Defence Force. Method: Data from a nationally representative household survey of Australian residents, the 2007 National Survey of Mental Health and Wellbeing, were used for this study. Results: Compared with community members, Australian Defence Force males were significantly more likely to have experienced not only deployment and other war-like events but also accidents or other unexpected events, and trauma to someone close. For non-deployed males, Australian Defence Force members were at increased risk of accidents or other unexpected events compared to community members. After controlling for the effect of potentially traumatic events that were more prevalent among all Australian Defence Force members, the increased risk of mental disorders among Australian Defence Force members was no longer evident. For non-deployed males, Australian Defence Force and community members were at comparable risk of poor mental health outcomes. A significant minority of Australian Defence Force members had onset of a mental disorder prior to their first deployment. Conclusions: Deployment and other potentially traumatic events among Australian Defence Force members can help to explain their increased vulnerability to mental disorders compared with community members. Providers should routinely enquire about a range of potentially traumatic events among serving and ex-serving military personnel.